PprM, a Cold Shock Domain-Containing Protein from Deinococcus radiodurans, Confers Oxidative Stress Tolerance to Escherichia coli - Park, Sun-Ha; Singh, Harinder; Appukuttan, Deepti; Jeong, Sunwook; Choi, Yong Jun; Jung, Jong-Hyun; Narumi, Issay; Lim, Sangyong (Frontiers in Microbiology, 2017)
Escherichia coli is a representative microorganism that is frequently used for industrial biotechnology; thus its cellular robustness should be enhanced for the widespread application of E. coli in biotechnology. Stress response genes from the extremely radioresistant bacterium Deinococcus radiodurans have been used to enhance the stress tolerance of E. coli. In the present study, we introduced the cold shock domain-containing protein PprM from D. radiodurans into E. coli and observed that the tolerance to hydrogen peroxide (H2O2) was significantly increased in recombinant strains (Ec-PprM). The overexpression of PprM in E. coli elevated the expression of some OxyR-dependent genes, which play important roles in oxidative stress tolerance. Particularly, mntH (manganese transporter) was activated by 9-fold in Ec-PprM, even in the absence of H2O2 stress, which induced a more than 2-fold increase in the Mn/Fe ratio compared with wild type. The reduced production of highly reactive hydroxyl radicals (·OH) and low protein carbonylation levels (a marker of oxidative damage) in Ec-PprM indicate that the increase in the Mn/Fe ratio contributes to the protection of cells from H2O2 stress. PprM also conferred H2O2 tolerance to E. coli in the absence of OxyR. We confirmed that the H2O2 tolerance of oxyR mutants reflected the activation of the ycgZ-ymgABC operon, whose expression is activated by H2O2 in an OxyR-independent manner. Thus, the results of the present study showed that PprM could be exploited to improve the robustness of E. coli.